Notes on the relationality in participatory researches with children and youth in/of the global south - Siqueira de Lara, Juliana; Pimentel Tumolo, Paula; Salvador Grisolia, Felipe; Dal Ongaro Savegnago, Sabrina (Revista de Psicologia, 2021)
The present article presents a series of reflections upon participatory research, focusing on the relationships established between children, young people and adults. Based on the different researches the authors have taken part in two universalisms often present in studies with children and young people are problematized. On the one hand, developmental psychology’s universalism objectifies children and young people as individuals who are less capable than, and in the process of acquiring rationality and identity. On the other hand, recent studies conducted mainly in the global North project the newer generations as autonomous beings that can clearly enunciate their voices and state their points of view, as long as the proper conditions to do so are guaranteed. In opposition to such universalisms, it is defended that the interdependent relationship between the researcher and the researchee produces both subjects, and that it is through this relationship that the research can be made participatory and relevant to those taking part in it.